Analisis Literasi Matematika Siswa SD: Bagaimana mereka menjawab Soal Asesmen Kompetensi Minimum (AKM)? - Iva Nurmawanti; Anindita SHM Kusuma (Program Studi Magister Pendidikan IPA, Universitas Mataram, 2023)
This study aimed to determine the ability of elementary school students' mathematical literacy in numbers, geometry, measurement, and algebra. The data from this research are in the form of quantitative data and qualitative data. Quantitative data was obtained from the results of students' mathematical literacy skills in answering 10 questions on each material. Quantitative data analysis used descriptive statistics and qualitative data analysis used qualitative study with a fixed comparison method. This research involved 50 students from two different elementary schools. A total of 20 students from SDN 42 Mataram and 30 from SDN 42 Cakranegara. The results obtained are low students' mathematical literacy skills. In the number material 80% of the students, in the algebra material 92% of the students, and in the geometry material 88% of the students scored less than equal to 50. In addition, it was found that in the usual and complex multiple choice questions the students answered questions on the Merdeka Teaching Platform (PMM), namely the AKM questions correctly, but after confirming the answers were only the origin of the answers. About 60% have difficulty understanding math literacy questions